2018
DOI: 10.1038/s41416-018-0100-3
|View full text |Cite
|
Sign up to set email alerts
|

Safety, anti-tumour activity, and pharmacokinetics of fixed-dose SHR-1210, an anti-PD-1 antibody in advanced solid tumours: a dose-escalation, phase 1 study

Abstract: Our results demonstrated a promising antitumour activity and a manageable safety profile of SHR-1210, displayed an explicit PK evidence of the feasibility of fixed dose, and established the foundation for further exploration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
112
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 135 publications
(121 citation statements)
references
References 31 publications
8
112
1
Order By: Relevance
“…13,14 Interstitial lung disease is an immune-mediated toxicity that resulted in the only drug-related death in this study, and this is consistent with the safety profile in a previous phase 1 study of nivolumab. 13,14 Interstitial lung disease is an immune-mediated toxicity that resulted in the only drug-related death in this study, and this is consistent with the safety profile in a previous phase 1 study of nivolumab.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…13,14 Interstitial lung disease is an immune-mediated toxicity that resulted in the only drug-related death in this study, and this is consistent with the safety profile in a previous phase 1 study of nivolumab. 13,14 Interstitial lung disease is an immune-mediated toxicity that resulted in the only drug-related death in this study, and this is consistent with the safety profile in a previous phase 1 study of nivolumab.…”
Section: Discussionsupporting
confidence: 88%
“…Most of the toxicity profiles in our study were similar to those previously reported for SHR-1210. 13,14 Interstitial lung disease is an immune-mediated toxicity that resulted in the only drug-related death in this study, and this is consistent with the safety profile in a previous phase 1 study of nivolumab. 15 The clinical manifestations of interstitial lung disease observed in this trial were similar to those previously reported with other anti-PD-1 antibodies in the treatment of advanced tumors.…”
Section: Discussionsupporting
confidence: 88%
“…In the third study, 36 patients with advanced melanoma or urinary tumors were enrolled, and 36 (100%) had grade 1-5 AEs, and the incidence of grade 3 and grade 3 AEs was 36%. SHR-1210 included four studies and 178 patients [146][147][148][149] . The study involved classic…”
Section: Fixed Effect Model Random Effects Modelmentioning
confidence: 99%
“…Tumor immunotherapy is an anticancer therapy with the goal of activating the immune system in the hope that its own immune function would inhibit tumor tissues [27]. At present, tumor immunotherapy has been shown to have strong antitumor activities in some tumor types, including melanoma and nonsmall cell lung cancer, and tumor immunotherapy drugs are clinically applied [28][29][30]. This study con rmed that ALOX12B, KRT78, RHOD, and ZNF750, which are related to tumor progression, affected the prognosis of CESC patients.…”
Section: Discussionmentioning
confidence: 99%